Innovative Activity of Business Managers as a Condition for Modernization of Regional Labour Potential - Belkin, Vladimir Nikiforovich; Belkina, Nadezhda Andreyevna; Antonova, Olga Anatolyevna (Economy of Regions, 2018)
The article discusses the problems of the innovative activity of managers in Russian enterprises as one of the conditions for the development of the labour potential of a region. The paper shows the main reasons for the low innovative activity of Russian enterprises. The systems of labour relations that have developed, as a rule, generate labour and innovative passivity as well as the opportunistic behaviour of managers. Most Russian enterprises lack incentive schemes for managers’ innovative activity. We propose a systematic approach to stimulating the innovative activity of managers, relying on the authors’ experience of researching the innovative activity of managers in a number of enterprises. The authors’ system «Innovation», which is a Russian version of the Japanese lean manufacturing system, stimulates the innovative activity of personnel. Implementing this system in the enterprises of the Ural Federal District has convincingly shown that in modern conditions, a radical increase in the innovative activity of business managers is possible. It, therefore, stimulates the development of regional labour potential. Our hypothesis is that a high innovative activity of managers in Russian enterprises is possible by developing and implementing a two-sided incentive system for stimulating managers’ innovative activity. Such a system should provide not only incentives for innovative activity but also managers’ responsibility for their innovative passivity. We suggest a system of concepts of the innovative activity of personnel, which is necessary when organizing work to stimulate the innovative activity of enterprise managers. For the first time in the theory of incentives for staff and practical activities of enterprises, we propose to introduce a semi-annual assessment of the innovative activity of managers. The assessment of managers’ innovative activity is an instrument for incentives for an enterprise. Moreover, for managers, it becomes one of the motivational factors for the manifestation of innovation activity. The research results were applied in the development of the System of Innovative Activity of Managers in GAG Uralelectromed and GAG Shadrinsky Auto Aggregate Plant. The results of the research can be applied in industrial enterprises of different legal status and forms of ownership.